Modelling and Cost Assessment of Hydrogen Production with Hybrid Energy Sources - Rahayu, Yeni Sri; Arianto, Supri; Suwarno, Suwarno (Journal of Mechanical Engineering, Science, and Innovation, 2025)
Green hydrogen production holds significant potential for supporting Indonesia's clean energy transition towards Net Zero Emissions (NZE) by 2060. However, its current Levelized Cost of Hydrogen (LCOH) of USD 4.3 to USD 8.3 per kilogram makes it less cost-effective than fossil fuel-derived hydrogen. This study aims to analyze the economics of a Hydrogen Plant (H2P) utilizing hybrid energy sources in Gresik. The methodology integrates advanced modeling techniques, including the Levelized Cost of Hydrogen (LCOH) and Net Present Value (NPV) analysis, to quantify production costs and assess long-term profitability. Data for this study was meticulously collected from a Hydrogen Plant in Gresik through historical operational records, technical specifications, projected energy demand, and meteorological data. By systematically comparing five alternative configurations: Grid+Solar PV (50,6 kWp), Grid+Solar PV (100 kWp), Grid+Solar PV (200 kWp), Grid+Solar PV (400 kWp), and Grid+Microhydro (76 kW). Configuration 5 was found to be the most economical under current assumptions, achieving the lowest LCOH of IDR 100.023/kg (USD 6,23/kg) and the highest NPV (IDR 22.935.241.285). This result is align with global decarbonization goals which are projected to be economically competitive at USD 2/kg by 2050.